Recommendations of the Polish Society of Gynaecologists and Obstetricians, Polish Paediatric Society, Polish Society of Family Medicine, Polish Society of Vaccinology, Polish Society of Oncological Gynaecology and Polish Society for Colposcopy and Cervical Pathophysiology on prophylactic vaccinations against infections with human papillomaviruses in Poland - Nowakowski, Andrzej; Jach, Robert; Szenborn, Leszek; Bidziński, Mariusz; Jackowska, Teresa; Kotarski, Jan; Mastalerz-Migas, Agnieszka; Nitsch-Osuch, Aneta; Pinkas, Jarosław; Sawicki, Włodzimierz; Sieroszewski, Piotr; Stukan, Maciej; et al. (Family Medicine & Primary Care Review, 2022)
Several hundred million people are infected with genital genotypes of the human papillomavirus (HPV) annually in the world. The infections transmitted mainly through sexual routes are usually asymptomatic, but can lead to the development of cervical, vulvar, vaginal, anal, penile cancers, some head and neck cancers and genital warts (condylomas). The fraction of HPV-related cancers ranges from nearly 100% in the case of cervical cancer to several/over a dozen percent in the case of other cancers and diseases. There are no effective drugs against HPV, but prophylactic HPV vaccines are available free of charge in immunisation programmes in many countries around the world. In Poland, HPV vaccinations have so far been executed out of pocket or in free-of-charge, local-governmental prevention programs, but the vaccination coverage of the target population does not exceed 10%. Starting in November 2021, one of the vaccines has been available with a 50% reimbursement, and work is underway to reimburse the next ones. The National Oncology Strategy assumes the implementation of the HPV immunisation programmes and vaccination of 60% of the teen population by 2028. Three prophylactic HPV vaccines are registered. All of them are safe and their effectiveness in the prevention of diseases caused by vaccine genotypes is almost 100% provided that full post-vaccination immunity is obtained before contact with the virus. Girls aged 11–13 are the priority target cohort for HPV vaccination in Poland. The implementation of routine, free-of-charge HPV immunisation in the Preventive Immunisation Program (PIP) for all adolescents should be pursued. Persons over the age of 13 may also benefit from HPV vaccination and should be vaccinated according to product specifications. In addition to free access under the PIP, the key element for the success of the implementation of HPV vaccinations in Poland will be the education of medical personnel and parents of adolescents to be vaccinated.